A novel ΔNp63-dependent immune mechanism improves prognosis of HPV-related head and neck cancer - Jana Mourtada; Jana Mourtada; Christelle Lony; Christelle Lony; Anaïs Nicol; Justine De Azevedo; Justine De Azevedo; Cyril Bour; Cyril Bour; Christine Macabre; Christine Macabre; Christine Macabre; et al. (Frontiers in Immunology, 2023)
BackgroundDeconvoluting the heterogenous prognosis of Human Papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OSCC) is crucial for enhancing patient care, given its rapidly increasing incidence in western countries and the adverse side effects of OSCC treatments.MethodsTranscriptomic data from HPV-positive OSCC samples were analyzed using unsupervised hierarchical clustering, and clinical relevance was evaluated using Kaplan-Meier analysis. HPV-positive OSCC cell line models were used in functional analyses and phenotypic assays to assess cell migration and invasion, response to cisplatin, and phagocytosis by macrophages in vitro.ResultsWe found, by transcriptomic analysis of HPV-positive OSCC samples, a ΔNp63 dependent molecular signature that is associated with patient prognosis. ΔNp63 was found to act as a tumor suppressor in HPV-positive OSCC at multiple levels. It inhibits cell migration and invasion, and favors response to chemotherapy. RNA-Seq analysis uncovered an unexpected regulation of genes, such as DKK3, which are involved in immune response-signalling pathways. In agreement with these observations, we found that ΔNp63 expression levels correlate with an enhanced anti-tumor immune environment in OSCC, and ΔNp63 promotes cancer cell phagocytosis by macrophages through a DKK3/NF-κB-dependent pathway.ConclusionOur findings are the first comprehensive identification of molecular mechanisms involved in the heterogeneous prognosis of HPV-positive OSCC, paving the way for much-needed biomarkers and targeted treatment.